2004
DOI: 10.1111/j.1365-2958.2004.04325.x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative oxygen‐dependent and oxygen‐independent ribonucleotide reductases in Streptomyces: cross‐regulation and physiological role in response to oxygen limitation

Abstract: SummaryRibonucleotide reductases (RNRs) catalyse the conversion of ribonucleotides to deoxyribonucleotides and are essential for de novo DNA synthesis and repair. Streptomyces spp. contain genes coding for two RNRs. We show here that the Streptomyces coelicolor M145 nrdAB genes encoding an oxygendependent class I RNR are co-transcribed with nrdS , which encodes an AraC-like regulatory protein. Likewise, the class II oxygen-independent RNR nrdJ gene forms an operon with a likely regulatory gene, nrdR , which en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 48 publications
1
53
0
3
Order By: Relevance
“…Our HU induction experiments also suggest that expression of class II RNR is not under vitamin B 12 control, as suggested for several other RNRs (28,39,40), because the addition of AdoCbl made no difference to the induction of nrdJ. Elegant studies in Streptomyces coelicolor recently identified the regulatory gene nrdR upstream of the nrdJ gene, forming an operon in this species (41). This regulatory protein is responsible for the coordinated transcription of class I and II RNRs in S. coelicolor.…”
Section: Figmentioning
confidence: 87%
See 2 more Smart Citations
“…Our HU induction experiments also suggest that expression of class II RNR is not under vitamin B 12 control, as suggested for several other RNRs (28,39,40), because the addition of AdoCbl made no difference to the induction of nrdJ. Elegant studies in Streptomyces coelicolor recently identified the regulatory gene nrdR upstream of the nrdJ gene, forming an operon in this species (41). This regulatory protein is responsible for the coordinated transcription of class I and II RNRs in S. coelicolor.…”
Section: Figmentioning
confidence: 87%
“…Apparently, the nrdR gene is ubiquitous and can be found together with, for example, the lexA operon in several other microorganisms (41). P. aeruginosa encodes an nrdR gene next to the rib genes for riboflavin biosynthesis (41,42). It is therefore premature to speculate on how the differential expression of class I and II RNR is controlled in P. aeruginosa, and further work is necessary to evaluate whether nrdR is involved in the transcriptional control of the RNRs also in this species.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The lexA gene (cg2114) of C. glutamicum ATCC 13032 is located in a head-to-head arrangement with the divS-nrdR (cg2113-cg2112) transcription unit (Fig. 1a), encoding a cell division suppressor and a regulator of deoxyribonucleotide biosynthesis (Borovok et al, 2004;Ogino et al, 2008;Rodionov & Gelfand, 2005). Downstream of the nrdR gene, a coding region for a putative ATP-dependent helicase has been predicted ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining genes encode hypothetical proteins with unknown functions, including secreted proteins, putative membrane proteins and potential transporters (Tables 2, 3 and 4). The only regulatory genes directly controlled by the LexA protein are lexA itself and the divergently oriented divS and nrdR genes, encoding a regulator of cell division and a DNA binding transcription regulator of ribonucleotide reductase, respectively (Borovok et al, 2004;Ogino et al, 2008;Rodionov & Gelfand, 2005). Interestingly, the three regulatory genes are located in a highly conserved gene region of the hitherto sequenced corynebacterial genomes (Fig.…”
Section: Verification Of Differential Gene Expression By Rt-pcr and Dmentioning
confidence: 99%